FILM PENDEK ‘IGNATIAN SERIES – CANNONBALL MOMENT’ SEBAGAI PEWARTAAN SPIRITUALITAS IGNASIAN BAGI ORANG MUDA KATOLIK - Cahyaningtyas, Angela Yovita Kristiani; Iswarahadi, SJ, Yoseph Ispuroyanto (Sanata Dharma University, 2023)
Short films can be used as a medium to introduce Ignatian Spirituality to young people. This research used the Ignatian Series short films as a medium to introduce Ignatian Spirituality. The aim of the research is to find out whether showing the Ignatian Series short films via YouTube is beneficial for young people to become more familiar with Ignatian Spirituality and accept it in everyday life. The subjects of this research were ten members of the Catholic Young People's organization (OMK) at Santo Antonius Padua Parish, Kotabaru. This research is descriptive qualitative research. Data was collected through observation, interviews and questionnaires. This research found that making the Ignatian Series short films was useful as a medium for reporting Ignatian Spirituality for the OMK of Santo Antonius Padua Parish, Kotabaru, Yogyakarta. After watching the Ignatian Series short film entitled Cannonball Moment, the research subjects had the intention to find out more about Ignatian Spirituality and participate in spreading it in everyday life.